Characteristic impairment of progesterone response in cultured cervical fibroblasts obtained from patients with refractory cervical insufficiency - Yosuke Sugita; Yoshimitsu Kuwabara; Akira Katayama; Shigeru Matsuda; Ichiro Manabe; Shunji Suzuki; Yumiko Oishi (Scientific Reports, 2023)
Abstract Preterm birth (PTB) is the leading cause of neonatal mortality, and reducing the PTB rate is one of the most critical issues in perinatal medicine. Cervical insufficiency (CI), a major cause of PTB, is characterised by premature cervical ripening in the second trimester, followed by recurrent pregnancy loss. Although multiple clinical trials have suggested that progesterone inhibits cervical ripening, no studies have focused on progesterone-induced molecular signalling in CI. Here, we established a primary culture system for human uterine cervical fibroblasts using a sample of patients with refractory innate CI who underwent transabdominal cervical cerclage and patients with low Bishop scores who underwent elective caesarean section as controls. RNA sequencing showed that the progesterone response observed in the control group was impaired in the CI group. This was consistent with the finding that progesterone receptor expression was markedly downregulated in CI. Furthermore, the inhibitory effect of progesterone on lipopolysaccharide-induced inflammatory stimuli was also impaired in CI. These results suggest that abnormal cervical ripening in CI is caused by the downregulation of progesterone signalling at the receptor level, and provide a novel insight into the molecular mechanism of PTB.